Peroxynitrite-mediated nitration of tyrosine residues in Escherichia coli glutamine synthetase mimics adenylylation: relevance to signal transduction. - Berlett, B S (1996)
Treatment of Escherichia coli glutamine synthetase (GS) with peroxynitrite leads to nitration of some tyrosine residues and conversion of some methionine residues to methionine sulfoxide (MSOX) residues. Nitration, but not MSOX formation, is stimulated by Fe-EDTA. In the absence of Fe-EDTA, nitration of only one tyrosine residue per subunit of unadenylylated GS leads to changes in divalent cation requirement, pH-activity profile, affinity for ADP, and susceptibility to feedback inhibition by end products (tryptophan, AMP, CTP), whereas nitration of one tyrosine residue per subunit in the adenylylated GS leads to complete loss of catalytic activity. In the presence of Fe-EDTA, nitration is a more random process: nitration of five to six tyrosine residues per subunit is needed to convert unadenylylated GS to the adenylylated configuration. These results and the fact that nitration of tyrosine residues is an irreversible process serve notice that the regulatory function of proteins that undergo phosphorylation or adenylylation in signal transduction cascades might be seriously compromised by peroxynitrite-promoted nitration.